2019
DOI: 10.1097/mph.0000000000001627
|View full text |Cite
|
Sign up to set email alerts
|

Cold External Temperatures and Sickle Cell Morbidity in Children: A Retrospective Analysis

Abstract: Background: Genetic and environmental factors affect the occurrence of vaso-occlusive crises (VOCs) in patients with sickle cell disease (SCD). Research provides inconsistent evidence on how environmental temperature affects SCD. Edmonton, Alberta, has an increasing SCD population and is the northern-most city in North America with a population of over a million. Objective: The objective of this study was to identify whether pediatric patients with SCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…High wind speed and low humidity were associated with changes in skin temperature and increased frequency of painful episodes 13–15 . Large temperature changes and seasonal viral infections, such as influenza, contributed to VOC 13,16,17 . A study conducted in Brazil 18 found that polluted air in the environment posed a significant threat to children with SCD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High wind speed and low humidity were associated with changes in skin temperature and increased frequency of painful episodes 13–15 . Large temperature changes and seasonal viral infections, such as influenza, contributed to VOC 13,16,17 . A study conducted in Brazil 18 found that polluted air in the environment posed a significant threat to children with SCD.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] Large temperature changes and seasonal viral infections, such as influenza, contributed to VOC. 13,16,17 A study conducted in Brazil 18 found that polluted air in the environment posed a significant threat to children with SCD. Air pollution caused by dust or pollen particles, and poisonous gases from car and truck exhaust (carbon monoxide, nitric acid, and ozone) was associated with frequent pain episodes.…”
Section: 31mentioning
confidence: 99%
“…The previous upper airway infection and/or changing environment from hot Ghana (about 30 o C) to a chillier Scandinavia (about 17 o C) [ 8 ] may have triggered the VOC in this otherwise healthy SCD patient. Before the current VOC, he had been little affected by the complications of his SCD; the last hospitalization was back in 2016.…”
Section: Discussionmentioning
confidence: 99%